A compact and ultra‐wideband three‐element quasi‐Yagi MIMO antenna system for wireless applications. Issue 5 (23rd February 2021) - Chaudhari, Amar D.; Ray, K. P.
Abstract: In this article, a new configuration of a compact planar three‐element multiple‐input‐multiple‐output (MIMO) antenna system is proposed based on quasi‐Yagi elements. A simple yet novel monopole driven three elements quasi‐Yagi antenna (QYA) is designed to obtain a directional pattern over an ultra‐wide bandwidth with a simple and compact configuration. The proposed single QYA contains the semi‐elliptical driven monopole, the flared truncated ground plane reflector, a single elongated elliptical director and a simple microstrip feedline. The simulated and measured results showed that the proposed MIMO antenna system operates in an ultra‐wide frequency range, starting from 1.53 to 6 GHz (118.7%, for |S11 | < −10 dB), which covers several wireless communication bands. It has a compact total electrical area of 0.21 λ 0 2 ( λ 0 is the highest operating wavelength) and a minimum isolation of 17 dB between its ports with a common ground plane without any complex decoupling structure. For each element, the measured peak gain and simulated total efficiency variations are between 3.3‐5.6 dBi and 77.6%–89%, respectively. There is good agreement between simulated and measured results. Furthermore, the calculated envelope correlation coefficient of < 0.006, channel capacity loss of < 0.2 bit/s/Hz, and stable total active reflection coefficient resonance are obtained over entire operating bandwidth, which conforms satisfactory MIMO/pattern diversity performance for wireless access‐point applications.